(untitled) - Pintel, Gerald (Englewood Cliffs, N.J., 1977)
This introduction to the principles and practices of retailing uses a straightforward approach to explore the major aspects of organizational structure, store locations, the buying function, merchandising, advertising and promotion, direct retailing, accounting, expenses, credit, research and careers. It addresses the fast-paced, broad-ranged changes that are confronting practitioners and examines the future that they face
Keywords: Retail trade,Bán lẻ; Management,Quản trị